A method for including diffusive effects in texture evolution. (April 2019) - Messner, Mark C.; Lebensohn, Ricardo A.; Zepeda-Alarcon, Eloisa; Barton, Nathan R.
Abstract: This work describes a model for representing grain misorientation in continuum models for texture evolution. The model relies on a connection, derived here, between the fluctuation of the reorientation velocity in discrete models of texture evolution and an isotropic diffusion operator that can be used to represent misorientation effects in continuum models for texture evolution. Previous work has developed a method for computing the fluctuation of the reorientation velocity in discrete models. These values, along with the average reorientation velocity, are used to set up inhomogeneous continuum advection and diffusion operators. The complete homogenized continuum model uses the discrete harmonics to represent and evolve the orientation distribution function, now including a diffusion operator representing the effects of intragranular misorientation. Results from the new model are compared to fully-resolved crystal plasticity finite element simulations and experimental data to demonstrate the accuracy of the proposed diffusion operator and the overall method for simulating texture evolution.